Epithelial morphogenesis in the Drosophila egg chamber requires Parvin and ILK - Keramidioti, Athina; Golegou, Evgenia; Psarra, Eleni; Paschalidis, Nikolaos; Kalodimou, Konstantina; Yamamoto, Shinya; Delidakis, Christos; Vakaloglou, Katerina M.; Zervas, Christos G. (Frontiers in Cell and Developmental Biology, 2022)
Integrins are the major family of transmembrane proteins that mediate cell-matrix adhesion and have a critical role in epithelial morphogenesis. Integrin function largely depends on the indirect connection of the integrin cytoplasmic tail to the actin cytoskeleton through an intracellular protein network, the integrin adhesome. What is currently unknown is the role of individual integrin adhesome components in epithelia dynamic reorganization. Drosophila egg chamber consists of the oocyte encircled by a monolayer of somatic follicle epithelial cells that undergo specific cell shape changes. Egg chamber morphogenesis depends on a developmental array of cell-cell and cell-matrix signalling events. Recent elegant work on the role of integrins in the Drosophila egg chamber has indicated their essential role in the early stages of oogenesis when the pre-follicle cells assemble into the follicle epithelium. Here, we have focused on the functional requirement of two key integrin adhesome components, Parvin and Integrin Linked Kinase (ILK). Both proteins are expressed in the developing ovary from pupae to the adult stage and display enriched expression in terminal filament and stalk cells, while their genetic removal from early germaria results in severe disruption of the subsequent oogenesis, leading to female sterility. Combining genetic mosaic analysis of available null alleles for both Parvin and Ilk with conditional rescue utilizing the UAS/Gal4 system, we found that Parvin and ILK are required in pre-follicle cells for germline cyst encapsulation and stalk cell morphogenesis. Collectively, we have uncovered novel developmental functions for both Parvin and ILK, which closely synergize with integrins in epithelia.